Earthquake Hazard Analysis of National Vital Objects by Probabilistic Seismic Hazard Analysis Method in West Java - Prayogo, Arif Zidan; Rorosanto, Zahrawani Ifada; Syahbana, Arifan Jaya; Maulita, Ika (Universitas Negeri Yogyakarta, 2025)
The Probabilistic Seismic Hazard Analysis (PSHA) method was used to analyze the level of earthquake hazard in West Java Province, Indonesia, which is located between two active tectonic plates. This research integrates literature study, earthquake data collection, and data processing to explore the influence of megathrust, background, fault, and combine earthquake sources on local and national vital objects in the region, such as Pusdik Kopassus, Presidential Palace, Cirebon PLTU, Geothermal Power Plant, Peacekeeping Mission Center (PMPP TNI), PT. PINDAD, PT DAHANA SUBANG, PLM GUNUNG SAWAL, Walahar Dam, PT Indonesia Power UJP Jabar 2 Pelabuhan Ratu, which have important roles in critical infrastructure, defense, and national resilience. The analysis shows variations in maximum ground acceleration between 0.40 g to 1.00 g for background earthquake sources, and 0.00 g to 1.00 g for fault earthquake sources. The research also underscores the importance of mitigation efforts and proper planning to reduce the potential impact of earthquakes in West Java, taking into account the crucial role of national vital objects in maintaining the stability and sustainability of the region. The implications of these findings reinforce the urgency to improve coordination between stakeholders in building earthquake resilience at the local and national levels, and highlight the importance of hazard curve analysis on national vital objects to inform the future of the region.